Beispiel Nr: 02
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ 3x^3+24 =0\\ \\ \textbf{Rechnung:} \\\\ 3x^3+24=0 3x^3+24 =0 \qquad /-24 \\ 3x^3= -24 \qquad /:3 \\ x^3=\displaystyle\frac{-24}{3} \\ x=\sqrt[3]{-8} \\ x=-2 \\ \text{Polynomdivision:}(-2)\\ \small \begin{matrix} ( 3x^3&&&+24&):( x +2 )= 3x^2 -6x +12 \\ \,-( 3x^3&+6x^2) \\ \hline &-6x^2&&+24&\\ &-(-6x^2&-12x) \\ \hline && 12x&+24&\\ &&-( 12x&+24) \\ \hline &&&0\\ \end{matrix} \\ \normalsize \\ 3x^{2}-6x+12 =0\\ x_{1/2}=\displaystyle\frac{+6 \pm\sqrt{\left(-6\right)^{2}-4 \cdot 3 \cdot 12}}{2\cdot3}\\ x_{1/2}=\displaystyle \frac{+6 \pm\sqrt{-108}}{6}\\ \text{Diskriminante negativ keine Lösung} \\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\$